Perilaku Siswa dalam Pencarian Informasi di Perpustakaan SMA Negeri 6 Padang - Siska Yuliana; Desriyeni Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This article discusses the behavior of students in the search for information in the library SMA 6 Padang. This paper was written to describe the Information Search Behavior Students in Senior High School Library 6 Padang. Based on data analysis, concluded the following things. Students in library information retrieval SMA 6 Padang can be seen through the following strategies are used: (a) the general students who visit the library to look for information purposes; (b) in search of information some students use the catalog to search for information; (c) the majority of students choose a book as the source of their information; (d) information retrieval became very important as an information service or library is how to meet the needs of the user requesting the information unit how to find the requested user information and helps users to find the desired information. Keywords: behavior; searches; information